2018
DOI: 10.1007/s10916-018-1131-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Workflow in Computed Tomography of the Chest

Abstract: A CT system with a tablet as mobile user interface and a wireless remote control for positioning and radiation release has recently been presented. Our aim was to evaluate the effects of a mobile CT examination workflow on the radiographers’ performance compared to conventional examinations. A prototype of a radiation protection cabin was installed besides the gantry of a CT system. The CT system was equipped with a simplified user interface on a portable tablet and a mobile remote control. 98 patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Wetzl et al. (21) reported a mean staff time (examination and post-processing time) of 14 min for chest CT examinations. This was longer than the median staff time reported in this study (10 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetzl et al. (21) reported a mean staff time (examination and post-processing time) of 14 min for chest CT examinations. This was longer than the median staff time reported in this study (10 min).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if a patient admitted to emergency department receives a CT examination for other purposes, performing an ULD-CT instead of sCXR will demand less time. Wetzl et al (21) reported a mean staff time (examination and postprocessing time) of 14 min for chest CT examinations. This was longer than the median staff time reported in this study (10 min).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous existing android applications related to computed tomography provide access to the patient's medical exams databases, see [1] and [2], manage data exchange and workflow in hospitals [3], work as a console to initiate data acquisition jobs, to control and finalize the scan or other procedures on the medical hardware they are tethered to [4], [5]. Until very recently, real, computation-intensive calculations rarely took place on a mobile device due to the lack of computational power and not-sostraightforward ways to organize the calculations behind the user interface.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, informed patient consent and patient anamnesis obtained during patient-physician interactions are still mainly archived in hard-copy form and remain unavailable for further use. Digitization has the potential to increase the efficiency of healthcare systems [1]: improved software technology and mobile devices, meanwhile, can help to spread this technology into hospitals [2][3][4][5]. Particularly in radiology departments, high levels of digitization are already common and necessary; however, PA and patients' current clinical problems are often incomplete, outdated, or inaccessible [6].…”
Section: Introductionmentioning
confidence: 99%